Stratification of Sphingosine Kinase-1 Expression and Activity in Rat Kidney - Facchinetti, Maria Marta (2008)
Sphingosine-1-phosphate, the product of sphingosine kinase (SK) activity, is a sphingolipid metabolite that regulates cell growth, survival and migration. It is also known to affect diuresis, natriuresis and renovascular contraction in rats, although the mechanisms through which it affects these processes are not known. No previous report has addressed the differences among the kidney zones regarding endogenous SK expression and activity. Therefore, we examined SK1 distribution and activity in the various kidney zones: cortex, medulla and papilla. We found that SK1 expression does not correlate with enzyme activity. Study of the expression showed that the enzyme is highly expressed in cortex, followed by medulla and papilla. However, medulla had the highest enzyme activity. In all kidney zones, SK1 expression was mainly cytosolic. Regarding enzyme activity, whereas we found no difference between cytosol, membrane and nucleus in renal medulla, the membrane-bound enzyme presented the highest activity in cortex and papilla. SK1 distribution observed by immunohistochemical staining showed higher expression in cortical proximal convoluted epithelial cells. In medulla, immunostaining was observed as patches of staining, whereas in papilla, positive immunostaining was exclusively restricted to collecting duct cells. We also evaluated the effects of bradykinin and angiotensin II on SK1 activity.